AN L-SYSTEM FOR MODELING OF UNIDIMENSIONALLY GROWING FLAT PLANT TISSUES - U. S. Zubairova; S. K. Golushko; A. V. Penenko; S. V. Nikolaev (Вавиловский журнал генетики и селекции, 2015)
In this work, a mathematical model and its implementation are proposed for computational simulation of one-dimensional symplastic growth of tissues. We modified the formal grammar of differential L-systems, and in this grammar, we described a dynamic model of symplastic growth with regard to its biomechanics. The results of the simulation of linear leaf blade growth are compared with those for a free-growing cell population. It is shown that in the model proposed symplastic growth causes a greater deviation of the actual cell length from its isosmotic length than in freely growing cells.